PECEIVED POLICE MISCONDUCTAND CONSUMERS SATISFACTION IN DELTA CENTRAL SENATORIAL DISTRICT, DELTA STATE (UNIZIK Journal of Marketing, 2026)
Abstract  The study carried out a research work on perceived police misconduct and consumers satisfaction in Delta Central Senatorial District, Delta State. The specific objectives of the study were to assess Police Bribery and Corruption, police Brutality and Police Indiscriminate Profiling on Consumers Satisfaction in Delta Central Senatorial District in Delta State, Nigeria. The study adopted the descriptive survey research design. The population of the study comprised of the population of the study comprised all consumers/citizens residing in four selected Local Government Areas (LGAs) out of the eight LGAs in Delta Central Senatorial District of Delta State, Nigeria. The Population of the study was 936, 979, NPC; 2006. The Taro Yarmen sample size formula was used to determine Sample for the study. Thus, the sample is 400. The study employed proportional stratified sampling tool to select respondents from the four (4) local Governments studied. The research instrument used for the study was the questionnaire and the Cronbach’s Alpa reliability test was used, the result of the test was 94.2%. Furthermore, Computer Programming (i.e., statistical package for social science (SPSS), Regression Analysis was used to test the hypotheses stated for the study. Descriptive statistics reveal a complex public view: while consumers generally express high trust in police (Mean = 3.9103), perceptions of police misconduct are prevalent, with brutality identified as the most pressing concern (Mean = 3.9401).
Keywords: Police Attitude, Police Bribery, Police Brutality, Indiscriminate Profiling & Consumer Satisfaction.